Engineering of high-performance textiles - Miao, Menghe; Xin, John H. (Duxford, United Kingdom Woodhead Publishing, 2018)
Engineering of High-Performance Textiles discusses the fiber-to-fabric engineering of various textile products. Each chapter focuses on practical guidelines and approaches for common issues in textile research and development. The book discusses high-performance fibers and yarns before presenting the engineering fabrics and architectures needed for particular properties required of high-performance textiles. Properties covered include moisture absorption, pilling resistant knitwear, fire retardant fabrics, camouflage fabrics, insect repellent fabrics, filtration, and many more. Coordinated by two highly distinguished editors, this book is a practical resource for all those engaged in textile research, development and production, for both traditional and new-generation textile products, and for academics involved in research into textile science and technology.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Textile fabrics; Textile fibers; Industrial fabrics; Textile fabrics -- Technological innovations; Electronic books